Harnessing social and collaborative tools in digital disaster response work: Implications for design and practice. (September 2021) - Gambo, Najeeb; Perry, Mark; Kashefi, Armin; Ayoung, Daniel Azerikatoa
This paper explores the implication of the use and appropriation of collaborative technologies in digital disaster response. Using a virtual ethnographic approach, we studied the work of Humanity Road through participant observation of seventeen response operations across thirteen countries for seventeen months. The results identify critical areas where collaborative technologies have been successfully deployed for organising disaster responses. Our analysis offers insights into the areas where these technologies have facilitated or hindered the capacity of cooperative work during response operations. We conclude by suggesting implications for design and practice.